Government Support to Public Private Partnerships : 2011 Highlights - Jett, Alexander Nicholas (World Bank, Washington, DC, 2014)
In FY 12, the Public Private Partnership (PPI) database expanded its coverage to create a flag to identify PPP projects and to expand its coverage to include government support to PPPs. To accomplish this, a new methodology was developed by the PPI Database team, which was reviewed by the global expert team on PPPs with members from the World Bank, International Finance Corporation (IFC) and Multilateral Investment Guarantee Agency (MIGA). The new coverage includes key financial data (where available) such as types of government guarantees; the debt-to-equity ratio; the amount of debt funding from commercial banks, donors and local banks; the names of banks providing loans; and government support to project revenues, including tax deductions. The core PPI database covers a broader range of private participation in infrastructure. For the purpose of tracking government support to PPPs, the following definition of PPPs was adopted.